Twenty-First Century "New" Greek Transnational Migration to Canada. Issue 1 (24th January 2022) - Tastsoglou, Evangelia
Abstract: This article derives from a qualitative study of the "new" migration from Greece to Canada, resulting from a severe socioeconomic crisis in Greece. Starting from the migration narratives of 20 "new" Greek migrants in Halifax and Toronto, this research focuses on how the "new" migrants make and carry out the decision to leave and immigrate to Canada. A heuristic use and reconceptualized understanding of the classic "push-pull" model, in conjunction with a transnational migration perspective, allows mapping out, through rich qualitative data, the structure—agency articulation in the "out-of-Greece-and-into-Canada" mobility of 21st century "new" Greek migrants.